1997
DOI: 10.1111/j.1745-6584.1997.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Plume Distortion and Apparent Attenuation Due to Concentration Averaging in Monitoring Wells

Abstract: Mathematical models that simulate common monitoring well sampling demonstrate the distortions that vertical concentration averaging causes during the mapping and modeling of an idealized, three‐dimensional contaminant plume emanating from a simple source of constant solute concentration. The apparent extent of the plume, mapped using simulations of a regular grid of screened monitoring wells, ranged from a worst case of 0% of the original plume area for long screens (4 m) in a low‐permeability formation to 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…This approximated solution can be easily derived by following the approach proposed in Domenico and Robbins (1985) and Martin-Hayden and Robbins (1997). Alternatively, the proposed solution can be obtained from the instantaneous pulse solution, by following the three steps defined in rules (A), (B), and (C) and by making some simplifying hypothesis.…”
Section: The Proposed 3d Solution For a Plane Source With Exponentialmentioning
confidence: 99%
See 1 more Smart Citation
“…This approximated solution can be easily derived by following the approach proposed in Domenico and Robbins (1985) and Martin-Hayden and Robbins (1997). Alternatively, the proposed solution can be obtained from the instantaneous pulse solution, by following the three steps defined in rules (A), (B), and (C) and by making some simplifying hypothesis.…”
Section: The Proposed 3d Solution For a Plane Source With Exponentialmentioning
confidence: 99%
“…The numerical solutions can introduce approximation errors, can be computationally demanding, and may explain why models using the same input parameters can generate very different results. Domenico and Robbins (1985), Domenico (1987), and Martin-Hayden and Robbins (1997) proposed some 3D approximated analytical solutions in closed form. The key advantage of the Domenico and Robbins (1985) approach and its derived extensions included in U.S. EPA tools as BIOSCREEN (Newell et al 1996), BIOCHLOR (Aziz et al 2000), currently used in risk assessment procedures, is that it provides a closedform solution that can be evaluated with much less significant numerical computations because it contains only complementary error functions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified how anomalous or otherwise unrepresentative results may be generated from traditional purge and sampling techniques (e.g. Robbins, 1989, Gibs andImbrigiotta, 1990;Reilly and Gibs, 1993;Conant et al, 1995;Church and Granato, 1996, Martin-Hayden and Robbins, 1997, Reilly and LeBlanc, 1998, Hutchins and Acree, 2000, Elci, et al, 2001. Common situations shown by these and other studies have caused investigators to question what traditional purge-and-sample ground water monitoring results represent.…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of misdirection from sampling data include partial penetration (Robbins, 1989;Martin-Hayden and Robbins, 1997;and Chaing et al, 1995) and lithologic heterogeneity . Anderson and others (1992) showed how DNAPL fingers and pools result in very strong dissolved contaminant stratification in an aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to study saltwater intrusion in coastal aquifers, for example geophysical methods [3], borehole investigations, and numerical models [4]. Borehole data are widely used in these kinds of studies, especially for calibrating numerical models, but in recent years the validity of data collected directly from wells and piezometers is under discussion [5][6][7][8][9]. Characterizing piezometric heads and salinity within a large coastal phreatic aquifer is a complex endeavour.…”
Section: Overviewmentioning
confidence: 99%